2022
DOI: 10.1111/bjso.12537
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in perceived COVID‐19 threat amid UK’s mass public vaccination programme coincide with reductions in outgroup avoidance (but not prejudice)

Abstract: It has long been proposed that perceptions of threat contribute to greater outgroup negativity. Much of the existing evidence on the threat–prejudice association in the real world, however, is cross‐sectional in nature. Such designs do not adequately capture individual‐level changes in constructs, and how changes in constructs relate to changes in other theoretically relevant constructs. The current research exploited the unique opportunity afforded by the mass COVID‐19 vaccination progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 89 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…Indeed, given that there is sizeable between‐country variability in right‐wing parties’ responses to the pandemic both in terms of narratives and policies (Wondreys & Mudde, 2022), future research should explore the influence of individual differences in political ideology among participants nested in other countries and subject to different political party framing. Please note that we also limited our analysis to White British participants in part because we did not have enough non‐Whites to confidently explore other British subgroups (for similar practice, see Meleady & Hodson, 2022; Zhao et al., 2022). Future research, including that in Britain, could expand consideration to other demographics to examine the generalizability of the findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, given that there is sizeable between‐country variability in right‐wing parties’ responses to the pandemic both in terms of narratives and policies (Wondreys & Mudde, 2022), future research should explore the influence of individual differences in political ideology among participants nested in other countries and subject to different political party framing. Please note that we also limited our analysis to White British participants in part because we did not have enough non‐Whites to confidently explore other British subgroups (for similar practice, see Meleady & Hodson, 2022; Zhao et al., 2022). Future research, including that in Britain, could expand consideration to other demographics to examine the generalizability of the findings.…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected from 400 participants from the online participant panel Prolific. Because the UK is largely White, we focused on White British participants only (for similar practice, see Meleady & Hodson, 2022; Zhao et al., 2022). Data from three mixed‐race and three non‐British participants were excluded.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence that COVID-19 led to a general increase in prejudice and discrimination towards out-groups is mixed. For example, one study found that a decrease in perceived COVID-19 threat following the UK's mass vaccination campaign was associated with lower out-group avoidance, but not with lower self-reported prejudice 97 . Another study found that participants who scored higher on disgust sensitivity and participants who perceived a greater risk of infection preferred to keep a greater distance from out-group members 98 .…”
Section: Prejudice and The Behavioural Immune Systemmentioning
confidence: 99%
“…Common Threat. We assessed the COVID-19 common threat using an adapted five-item common threat scale (Adam-Troian & Bagci, 2021;Meleady & Hodson, 2022; for example, ''COVID-19 constitutes a threat across the country''; 1 = strongly disagree, 7 = strongly agree). Higher scores represent a greater common threat (a = .74).…”
Section: Procedures and Materialsmentioning
confidence: 99%